2015
DOI: 10.1371/journal.pone.0118694
|View full text |Cite
|
Sign up to set email alerts
|

Diastolic Dysfunction Is an Independent Predictor of Cardiovascular Events in Incident Dialysis Patients with Preserved Systolic Function

Abstract: BackgroundDiastolic heart failure (HF), the prevalence of which is gradually increasing, is associated with cardiovascular (CV) morbidity and mortality in the general population and, more specifically, in patients with end-stage renal disease (ESRD). However, the impact of diastolic dysfunction on CV outcomes has not been studied in incident dialysis patients with preserved systolic function.MethodsThis prospective observational cohort study investigates the clinical consequence of diastolic dysfunction and th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
32
0
2

Year Published

2016
2016
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 44 publications
(37 citation statements)
references
References 42 publications
1
32
0
2
Order By: Relevance
“…It must therefore be suspected that HFpEF is highly prevalent in HD patients. Yet, although it has recently been shown that diastolic dysfunction is predictive of cardiovascular events in incident HD patients [17], its true prevalence, associated factors and clinical outcomes are still unknown. In the light of future therapeutic options it is essential that these patients are identified easily, categorized correctly and characterized thoroughly in order to enable optimal care.…”
Section: Introductionmentioning
confidence: 99%
“…It must therefore be suspected that HFpEF is highly prevalent in HD patients. Yet, although it has recently been shown that diastolic dysfunction is predictive of cardiovascular events in incident HD patients [17], its true prevalence, associated factors and clinical outcomes are still unknown. In the light of future therapeutic options it is essential that these patients are identified easily, categorized correctly and characterized thoroughly in order to enable optimal care.…”
Section: Introductionmentioning
confidence: 99%
“…In the assessment of diastolic function, several parameters and different criteria have been used for evaluations, and a relationship with patient prognosis and several parameters has been verified in a general population [20, 21] as well as in a dialysis population [8-10]. The prevalence and grades of DD have a prognostic impact [22], with a progressively increased risk of mortality being observed with the progression of DD [20], even in patients with a preserved LVEF [21].…”
Section: Discussion/conclusionmentioning
confidence: 99%
“…LVDD and HFpEF are more prevalent than HFrEF in maintenance hemodialysis patients [7]. Previous studies identified diastolic dysfunction (DD), defined as an increased ratio of early mitral flow velocity (E) to early mitral annulus velocity (E’) (E/E’) and/or a high left atrium volume index, as an independent predictor of mortality in starting and chronic dialysis patients [8-10]. Therefore, echocardiography needs to be employed to confirm cardiovascular risks and guide treatments for ESRD patients on dialysis.…”
Section: Introductionmentioning
confidence: 99%
“…Program hronične HD vremenom poveća-va vrijednosti plućnog pritiska, a disfunkcija desne komore je glavni uzrok smrti pacijenata sa terminalnom bolesti bubrega [1][2][3][4][5].…”
Section: Uvodunclassified